PENGATURAN PIDANA MINIMUM KHUSUS DALAM UNDANG-UNDANG NO. 31 TAHUN 1999 JO UNDANG-UNDANG NO. 20 TAHUN 2001 TENTANG TINDAK PIDANA KORUPSI - Suandi Yaya Manuaba, Ida Bagus; -, Adiwati (Kertha Wicara : Journal Ilmu Hukum, 2014)
In the contacts of law enforcement towards coruption which is categorize as extraordinary crime which resulting in social gap, economy, the lost of faith towards the government and various problems which led to the bear of law no. 31 of 1999 jo law no. 20 of 2001 about coruption. The determination of minimum sanction in the regulation of coruption is an effort to arrange regulation for the eradication of corruption in Indonesia where in the regulation there has not been any guidelines and regulation towards the minimum sanction. The purpose of this wrinting is to acknowledge how the judge verdict the minimum sanction toward the actor of coruption without using the guidelines of specific minimum sanction, the judge could use interpretation methods through law findings towards norms which has not existed before.
Keywords: PENGATURAN PIDANA MINIMUM KHUSUS DALAM UNDANG-UNDANG NO. 31 TAHUN 1999 JO UNDANG-UNDANG NO. 20 TAHUN 2001 TENTANG TINDAK PIDANA KORUPSI